Strategi Pengembangan Usaha Air Minum Dalam Kemasan (Studi Kasus PT. Satyaloka Tirta Amerta Bangli) - Panglewai, Yugo Leonardo; Mahatma Tuningrat, Ida Ayu; Satriawan, I Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 4 (2015): Desember)
This research was aimed at analyzing the internal and external condition of packaged mineral water as well as organizing some advices about possible strategies in developing the production of packaged mineral water at PT. Satyaloka Tirta Amerta. Research method used in collecting data was Delphi and the method used in processing and analyzing the data acquired was approach in management strategic concept. The result of this research showed that there were 9 strengths, 7 weaknesses, 5 possibilities, and 1 threat. Moreover, the result acquired also showed that the matrix Internal Factor Evaluation (IFE) was 3.122 and the matrix External Factor Evaluation (EFE) was 3.636. This value indicated the strong position in matrix internal external (IE). However, the strategy should be implemented was incentive and integrative strategy. On the other hand, based on SWOT analysis, there were 7 alternative strategies that could be implemented to develop the industry of PT. Satyaloka Tirta Amerta.
Keywords: 68,